Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 2 - Derivatives - 2.5 The Chain Rule - 2.5 Exercises - Page 158: 46



Work Step by Step

$$y'=\left((x+(x+\sin^2x)^3)^4\right)'= 4(x+(x+\sin^2x)^3)^3\cdot((x+(x+\sin^2x)^3)'= 4(x+(x+\sin^2x)^3)^3\cdot(1+3(x+\sin^2x)^2\cdot(x+\sin^2x)')= 4(x+(x+\sin^2x)^3)^3(1+3(x+\sin^2x)^2(1+2\sin x\cdot(\sin x)'))= 4(x+(x+\sin^2x)^3)^3(1+3(x+\sin^2x)^2(1+2\sin x\cos x))= 4(x+(x+\sin^2x)^3)^3(1+3(x+\sin^2x)^2(1+\sin2x))$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.